Liquefaction of Mukah Balingian low rank coal using semi-continuous solvent flow reactor system / Nur Nasulhah Kasim - Kasim, Nur Nasulhah (2010)
Direct coal liquefaction on un-irradiated and microwave irradiated Mukah Balingian (MB) coal were successfully carried out in semi-continuous solvent flow reactor system at temperature and pressure of 300 - 450 °C and 4 MPa, respectively, using tetralin as hydrogen-donor solvent. The coal conversion, oil+gas, asphaltene and preasphaltene for un-irradiated coal sample obtained at optimum condition using response surface methodology (RSM) i.e., solvent flow rate of 7 ml min-1 and soaking time for 60 min, were 81%, 62%, 9% and 10%, respectively. It was observed that solvent flow rate and soaking time seem to have minimum influence on the coal conversion and oil+gas yield. In this study, microwave irradiation pretreatment was also applied on MB coal at power of 600W for 1 min. In the microwave irradiation pretreatment, as solvent flow rate increased from 7 to 15 ml min-1, slightly higher amount of coal conversion was obtained with comparison to the un-irradiated coal sample. The increased in solvent flow rate also resulted to an increased in percentages of asphaltene and preasphaltene with exception to the solvent flow rate of 10 ml min-1, that was due to conversion of these materials to oil+gas. There are two reasons for this observation i.e., insufficient of solvent at solvent flow rate of 7 ml min-1 and insufficient time of free radical reaction occurred during the liquefaction process at solvent flow rate of 15 ml min-1. The increased in coal conversion and oil+gas yield at solvent flow rate of 10 ml min-1 might due to the sufficient amount of the solvent to penetrate deeply into the coal macropores to cap the radicals instantaneously, and promote the volatile matter released from coal to produce light molecular weight product i.e., oil+gas. Coal liquefaction process of un-irradiated and microwave irradiated coal was being proposed using this reactor system. There are three stages that were monitored during the liquefaction process i.e., heating up, isothermal and free radical reaction stage. The asphaltene and preasphaltene could be obtained at heating up stage for both samples. Thus, it shows that the extraction process predominant at lower temperature of liquefaction process. Two reactions occurred at isothermal stage i.e., extraction and free radical reaction due to the oil+gas increased with reduction of asphaltene and preasphaltene as solvent flow rate increased. As temperature increased from 400 ~ 450 °C, insufficient of solvent might increase the formation asphaltene and preasphaltene and promote the retrogressive reaction to occur. Sufficient amount of solvent available to stabilize the free radical species resulted higher amount of oil+gas obtained during this stage. In brief, free radical reaction predominant at this stage to increased coal conversion and oil+gas yield. Thus, the semi-continuous solvent flow reactor system could be a promising approach in understanding coal liquefaction process at lower and higher liquefaction temperatures.